Divergence of the third harmonic stress response to oscillatory strain approaching the glass transition. Issue 43 (18th October 2016) - Seyboldt, Rabea; Merger, Dimitri; Coupette, Fabian; Siebenbürger, Miriam; Ballauff, Matthias; Wilhelm, Manfred; Fuchs, Matthias
Abstract : The nonlinear stress response at the third harmonic in a periodically strained colloidal dispersion is studied. It diverges at the glass transition indicating the in-stability of the transient elastic structure. Abstract : The leading nonlinear stress response in a periodically strained concentrated colloidal dispersion is studied experimentally and by theory. A thermosensitive microgel dispersion serves as well-characterized glass-forming model, where the stress response at the first higher harmonic frequency (3 ω for strain at frequency ω ) is investigated in the limit of small amplitude. The intrinsic nonlinearity at the third harmonic exhibits a scaling behavior which has a maximum in an intermediate frequency window and diverges when approaching the glass transition. It captures the (in-) stability of the transient elastic structure. Elastic stresses in-phase with the third power of the strain dominate the scaling. Our results qualitatively differ from previously derived scaling behavior in dielectric spectroscopy of supercooled molecular liquids. This might indicate a dependence of the nonlinear response on the symmetry of the external driving under time reversal.